AREA SCALE EVALUATION OF SUMITHION (OMS-43) FOR CONTROL OF ADULT ANOPHELINE MOSQUITOES IN SOUTHERN IRAN - N.Eshghy; A.Mesghali; Gh. Behbahani; M.Motabar (Tehran University of Medical Sciences, 1973)
A field trial evaluation of Sumithion (OMS-43) was carried out (1972) in the Mamasani area, Kazeroun, Southern Iran, in order to evaluate the effectiveness of this insecticide for the control of adult anopheline mosquitoes.The technical difficulties encountered in the area and related to malaria were the resistance of A. stephensi to DDT and Dieldrin, the exophilic and exophagic habits of A. d'thali, A. superpictus and A. fluviatilos and the ecology of the inhabitants.Sumithion spraying, wdp, 2 g/m2, covered 57 villages with a population of 11,445.One round of spraying was implemented in August at the peak of activity of A. stephensi. The effectiveness of Sumition was evaluated by pyrethrum spray, exit trap, night bait and outdoor ollections, as well as by age determination of female mosquitoes and biological evaluation.Pyrethrum spray catches showed a remarkable reduction in indoor resting density of A. stephensi. Exit trap observations indicated 100% mortality within a 24- hour recovery period. The man biting rate was reduced during the course of collection. On the basis of the results obtained, it was concluded that Sumithion is an effective insecticide against anopheline mosquitoes and controls A. stephensi, under the conditions of this experiment, for about two months.